APAKAH RELIABILITY DAN DURABILITY DAPAT MEMBENTUK BRAND LOYALTY ? STUDI PADA PRODUK APPLE DI JAKARTA - Martinus Ega Narendra (Prosiding Working Papers Series In Management, 2018)
Technology advancement and development nowadays are increasing the demand of smart phone from year to year; this situation increases the competition in the smart phone industry. Because of that, smart phone companies are being pushed to make and to develop a product that’s easy to remember, easy to recognize and has the quality that meets consumer’s expectations. One of many smart phone companies in the world right now is Apple with their Apple iPhone product.This research uses 200 samples of Apple iPhone users that were visiting eStore at Pondok Indah Mall, samples were taken by using simple random sampling method and the data was collected by spreading questionnaires to the respondents. The collected data is processed and analyzed by using IBM SPSS STATISTICS 23 and LISREL 8.80.The result of this research showed that reliability and durability have direct effects on perceived quality and indirect effects on brand loyalty through perceived quality. Keywords: smart phone, reliability, durability, perceived quality, brand loyalty.